La debida diligencia en los trámites notariales de personas con discapacidad - Naula Anilema, Yesenia Marisol (2025)
he Constitution of Ecuador, along with international treaties and conventions, recognizes and guarantees the rights of people with disabilities across different areas and institutions, both public and private. One of these institutions is the notary offices around the country, represented by notaries who are part of the judicial system. This research focuses on the due diligence required in notarial procedures involving people with disabilities. The main objective was to analyze the legal requirements for carrying out notarial procedures for people with physical, intellectual, and psychosocial disabilities. A qualitative methodology was used, including interviews with notaries and professionals in the notarial field, as well as documentary analysis based on the review and interpretation of various legal and doctrinal bibliographic sources. Additionally, a comparative analysis with Spain was conducted, which provided valuable insights for this study. The research begins by clearly defining what disability is and identifying the legally recognized types of disability. Ultimately, the notary holds the responsibility of verifying the legal capacity of the parties involved, which is the primary requirement. Furthermore, the creation of regulations, protocols, and guidelines is necessary to ensure equal rights. Support materials should be available to guide notaries on when and how to conduct notarial acts involving people with disabilities, without violating their rights.